Design of a bridge health index for prioritization of technical interventions in Costa Rica - Ortiz-Quesada, Giannina (2024)
Currently, Costa Rica does not count with a rigorous methodology that considers the proper variables required to assess the structural health condition of bridges. Some institutions use different criteria in order to assign a rating to the evaluation of a structure and this generates different results when prioritizing interventions.  The prioritization of road infrastructure projects is key to invest resources in the most efficient way possible. In this context, this article presents a proposal that seeks to standardize an index for the structural health condition of bridges, which allows prioritizing and allocating resources objectively.  For this index, the evaluation of the structural condition of critical elements is used, as well as risk matrices related to seismic and hydrometeorological hazards.  As a result, the design of this index involves the analysis of a large number of variables through technical and statistical criteria.